Effects of explosive pressure on cadaveric ovine auditory tissue - McCann, Amanda, author; Heyliger, Paul, advisor; Mahmoud, Hussam, committee member; McGilvray, Kirk, committee member (Colorado State University. Libraries, 2018)
The focus of this research centered around two main goals: 1) determine the allowable pressures that people can be exposed to in non-life-threatening situations and 2) determine the pressure required to rupture a sheep eardrum as a representative sample for human ears. For the first goal, blast pressure tests were conducted at a local football stadium using Composition 1 (C1) plastic explosive, 50-grain detonation cord, and the game cannon firing 75% strength shells. The results for each explosive were put into units of TNT equivalency to provide a common unit between explosive types. Based on the recorded pressures, spectators and staff in the vicinity of the game cannon are not at risk of severe ear damage, but should still take precautions and wear hearing protection when in the vicinity. The second goal, which forms the bulk of this thesis, was investigated through conducting two series of explosive tests on dissected sheep heads and sheep ears as a representative sample for human ears. Through these experiments, the author developed a refined process for preparing and analyzing the eardrum samples under blast conditions. From these two blast tests, eight eardrums were ruptured when exposed to varying explosive pressures and this damage was used to estimate the threshold pressure at which severe damage initially occurs. The threshold pressure for these experiments is within the range of 34 kPa (4.9psi) to 42 kPa (6.1psi), which is substantially refined compared to the range of 8 kPa (1.2psi) to 104 kPa (15.1 psi) listed in other published literature. At this time, this result is only accurate for deceased sheep eardrum ruptures, but further testing could verify that this is applicable to humans.
Keywords: effects; ovine; sheep; explosive; auditory; pressure